2016
DOI: 10.1186/s12877-016-0359-2
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of family members in the nursing home to hospital transfer decision

Abstract: BackgroundThe objective of this study was to better understand the experiences of family members in the nursing home to hospital transfer decision making process.Semi-structured interviews were conducted with 20 family members who had recently been involved in a nursing home to hospital transfer decision.ResultsFamily members perceived themselves to play an advocacy role in their resident’s care and interview themes clustered within three over-arching categories: Family perception of the nursing home’s capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1
5

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 19 publications
1
52
1
5
Order By: Relevance
“…Thirty-one studies considered stakeholder experiences in more detail. Stakeholders experienced various situations in urgent care: from hospitalisation decisions, 35 37 54 to withholding treatment at the end of life, 29 37 58 59 to prescribing antibiotics. 57 58 60 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-one studies considered stakeholder experiences in more detail. Stakeholders experienced various situations in urgent care: from hospitalisation decisions, 35 37 54 to withholding treatment at the end of life, 29 37 58 59 to prescribing antibiotics. 57 58 60 …”
Section: Resultsmentioning
confidence: 99%
“… 53 There were also barriers identified by professionals, with reports from care facility and emergency department staff of carers directly contradicting instructions in advance care plans, ordering more burdensome interventions. 35 59 69 Medical professionals were seen to take the lead in decision making in urgent care. 29 37 Involvement of informal carers was reported to lead to more aggressive treatment, for example, carer awareness of infection episodes for people with dementia in care homes lead to increased hospital transfers.…”
Section: Resultsmentioning
confidence: 99%
“…None of the articles describe utilising evidence to help residents or their families decide on treatment options. Two studies found a lack of provision of information to residents and their families, and reported that staff rarely discussed the risks and benefits of treatment options [28] [38]. Some families indicated that there was a lack of information provided to them to assist in decision making [33].…”
Section: Evidenced-based Practicementioning
confidence: 99%
“…Education in SDM was recommended in two studies, [28] [38] particularly about the importance of family involvement. The articles analysed which utilised an educational intervention were predominantly quantitative approaches [40] [43]…”
Section: Educationmentioning
confidence: 99%
See 1 more Smart Citation